Microencapsulated tuna oil results in higher absorption of DHA in toddlers - Fard, Samaneh Ghasemi; Loh, Su Peng; Turchini, Giovanni M.; Bo, Wang; Elliott, Glenn; Sinclair, Andrew J. (MDPI, 2020)
Docosahexaenoic acid (DHA) is an essential component for brain and visual acuity development during foetal and early postnatal life. A newly released directive under the European Commission stipulates DHA as a mandatory ingredient in infant formula. This poses challenges to manufacturers in preserving the stability and bioavailability of DHA at levels akin to human breast milk. The aims of this study were (a) to investigate the bioavailability of microencapsulated omega-3 DHA formulations in healthy toddlers compared with high DHA fish oil for a one-month period and (b) to assess the effect of DHA supplementation on children’s sleep and cry patterns. Sixty toddlers were randomly allocated to four groups: 1. unfortified formula, 2. unfortified formula plus high DHA tuna oil, 3. fortified formula with dairy-based microencapsulated high DHA tuna oil powder, and 4. fortified formula with allergenic-free microencapsulated high DHA tuna oil powder. Bioavailability was assessed from both blood and faecal fatty acid levels. The results showed an enhanced bioavailability with significantly greater concentrations of blood DHA levels in formulas with microencapsulated powders. There were no significant effects of treatment on sleep and cry patterns. Application and delivery of microencapsulated DHA tuna oil powder in toddlers’ formula provided better bioavailability of the active DHA.